2009 International Conference on Computational Science and Its Applications 2009
DOI: 10.1109/iccsa.2009.25
|View full text |Cite
|
Sign up to set email alerts
|

Recovering 3D Shape of Weak Textured Surfaces

Abstract: 3D shape recovery of the object from its 2D images based on Image Focus has been an important field of research. Shape from Focus (SFF) is one of the passive methods to recover the shape of the object. Mostly, existing approaches work well with dense textured objects; however, they cannot compute depth of weak textured scenes with great precision. In this paper, we propose a new SFF algorithm which improves the recovered shape of weak textured objects. The proposed method is experimented and its performance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…[5]), over differently shaped kernels, to nonlinear filtering as proposed in [6]. In [7,8], the authors proposed to detect regions with a high variance in the depth map and suggested to smooth the depth in these parts by interpolation. Pertuz, Puig, and Garcia analyzed the behavior of the contrast curve in order to identify and remove low-reliability regions of the depth map in [9].…”
Section: Introductionmentioning
confidence: 99%
“…[5]), over differently shaped kernels, to nonlinear filtering as proposed in [6]. In [7,8], the authors proposed to detect regions with a high variance in the depth map and suggested to smooth the depth in these parts by interpolation. Pertuz, Puig, and Garcia analyzed the behavior of the contrast curve in order to identify and remove low-reliability regions of the depth map in [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several algorithms and operators have been proposed for this purpose. The most popular operators are the Modified Laplacian [8], the Tenengrad Algorithm [23] and the GrayLevel Variance [20], among others [24]. In the present work, the Modified Laplacian is used as the focus measure:…”
Section: Focus Measurementioning
confidence: 99%
“…Adaboost is then used to combine each weak classifier in order to obtain the best classification rate in the training set. 2 In the experiments, a total of five filtering algorithms have been used in the comparisons: the Canny edge detector-based algorithm proposed in [22] (CAN), the mean response of the Gabor filters (GAB), the combination of Gabor filters using Adaboost (G+AD), the depth-map filtering-based algorithm proposed in [20] (DFIL) and the proposed reliability-based method (R2). In order to compare the effect of only the filtering stage of these approaches, all the depth-maps have been computed with the same SFF algorithm [7].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Amb aquest mètode, es basa en detectar la textura present de la mostra que es vol mesurar. Amb aquest mètode, es captura una imatge de camp clar, i un algoritme anomenat operador de focus (Focus Operator) [23] és capaç d'extreure la posició axial del focus per a cada píxel de la imatge. Quan la superfície està en focus la seva textura està ben definida en la imatge i l'operador detecta un senyal elevat, mentre que si la superfície està fora de focus, la imatge està borrosa i el senyal detectat per l'operador es redueix dràsticament.…”
Section: Texturització Artificialunclassified